Studi Numerik Pengaruh Jarak Silinder Pengganggu Pada Sisi Returning Blade Terhadap Coefficient of Power (Cp) Turbin Angin Savonius Overlap - Fariz Andika Firmansyah; Priyo Agus Setiawan; Projek Priyonggo Sumangun (Politeknik Perkapalan Negeri Surabaya, 2023)
The coefficient of power Savonius wind turbine improved in experimental studies that added overlap and variation in the distance of the disruptive cylinder in front of the returning blade. However, further research needs to be done to validate the experimental results. This research is in the form of a numerical study using the 3-dimensional Computational Fluid Dynamics (CFD) method. In this simulation, the solver chosen is pressure based with a transient time mode. In addition, the model used is the k-epsilon realizable model. Simulations were carried out to determine the value of the coefficient of power the turbine. The turbine has the same diameter and height of 0.4 meters with the addition of overlap. The variation in the distance of the disruptive cylinder used is S/d = 1.4; S/d = 1.7; S/d = 2 and S/d = 2.3. The final result shows that the performance of the turbine can reach the highest increase of 3.51% compared with overlapped Savonius wind turbine without cylinder at a distance of S/d = 1.7. The coefficient of power (Cp) value is 0.324 at Tip Speed Ratio 1.